Synthesis of Antimicrobial and Antioxidant Zinc Oxide Hydrogel for Drug Delivery Applications - Ramesh, Krithika; Ponnusamy, Jeyanthi; Periasamy, Pazhanisamy (Indonesian Journal of Chemistry, 2024)
A novel and simple method was used to synthesize antimicrobial and antioxidant porous (N-tert-butylacrylamide-co-N-vinylpyrrolidone) zinc oxide hydrogel via free radical copolymerization. The hydrogel was characterized by NMR, XRD, and SEM. Thermodynamic properties of the hydrogel were described quantitatively by the Flory-Rehner method. The results indicate that the synthesized hydrogel exhibits strong antioxidant activity, making it a potential candidate for use in preventing degenerative diseases. The antimicrobial tests showed that the hydrogel could inhibit the growth of Gram-positive and Gram-negative bacteria, as well as some pathogenic bacteria and fungi. The inhibition zones ranged from 10 to 15 mm for bacteria and from 5.2 to 9.1 mm for fungi. The reactivity ratio r1 × r2 equal to 1 confirmed ideal copolymerization showed the composition of the copolymer and the comonomer feed are same. The hydrogel's structure and reactivity are significant for constructing effective delivery systems for specific applications. Optimizing the monomer proportion could enhance hydrogel efficiency and release behavior. The hydrogel's water solubility, non-toxicity, and antioxidant properties suggest it could be safe and effective throughout the drug delivery process, contributing both passive and reactive targeting functions.